Titania-heteropolyacid composites (TiO2-HPA) as catalyst for the green oxidation of trimethylphenol to 2,3,5-trimethyl-p-benzoquinone - Palacio, Magdalena (2020)
New catalysts containing phosphomolybdic acid (PMA) and vanadophosphomolybdic acid (VPMA) in a titania matrix were synthesized by the sol–gel process with different heteropolyacid loads (5%, 15%, and 30% (w/w): 5PMA-TiO2, 15PMA-TiO2, 30PMA-TiO2, 5VPMA-TiO2, 15VPMA-TiO2, and 30VPMA-TiO2). The techniques used to characterize the materials were XRD, DRS, SEM, FT-IR, 31P MAS-NMR, potentiometric titration with n-butylamine, and N2 physisorption at −196 °C. The materials were used as heterogeneous catalysts in the oxidation of 2,3,6-trimethylphenol (TMP) to 2,3,5-trimethyl-p-benzoquinone (TMBQ), a key intermediate in vitamin E synthesis. The catalysts allowed an ecofriendly TMBQ synthesis, using ethanol as solvent and aqueous hydrogen peroxide as a clean oxidizing agent, at room temperature. The conversion of TMP reached 90% and 99% for the samples with 15PMA-TiO2 and 15VPMA-TiO2, respectively, after 4 h. The amount of Mo and V in the reaction medium was determined by ICP-MS, which showed leaching of only 17–18% Mo, but 48% V. Reuse of the catalysts was performed. For 15PMA-TiO2, the conversion was maintained in the second cycle. A homolytic mechanism was proposed for TMBQ synthesis, which involved the formation of a peroxometallic species through an HPA-Ti center.